Women Scholars, Integration, and the Marianist Tradition: Learning From Our Culture and Ourselves - Seery, Mary Ellen; Adams, Shauna M.; Kinnucan-Welsch, Kathryn; Bowman, Connie L.; Grogan, Patricia R.; Joseph, Laurice J. (Catholic Education: A Journal of Inquiry and Practice, 2002)
In the fall of 1997, a group of junior tenure-track women faculty in the Department of Teacher Education at the University of Dayton decided to meet regularly in order to support each others’ scholarly endeavors in the process of achieving promotion and tenure. The group of subsequently became known as the Writing ”“Writers’ Support Group (WWSG). In 2000, the group conducted a self-study of its group process to determine how the formation of women’s WWSG fit with the mission and characteristics of a Marianist university. The results suggest that, although each of the characteristics could be identified in the group processes, the group best identified with the Marianist mandate to educate in family spirit. Each member of the group considered the possible reasons for this outcome.